Apixaban or rivaroxaban in the treatment of acute venous thromboembolism? - Hellfritzsch, Maja; Grove, Erik L.; Adelborg, Kasper (Annals of Translational Medicine, 2019)
Venous thromboembolism (VTE) may affects all parts of the venous circulation, but frequently manifests as deep vein thrombosis or pulmonary embolism. Annually, around 10 million cases are diagnosed worldwide, and VTE constitutes a growing global health burden with increasing incidence and prevalence (1,2). VTE is associated with substantial morbidity and mortality, and about 30% of all patients with VTE experience a recurrent event within 10 years (3). Traditionally, vitamin K antagonists (VKA) have been the cornerstone in the treatment of patients with VTE, but the emergence of direct oral anticoagulants (DOAC; dabigatran, rivaroxaban, apixaban, and edoxaban) has led to a substantial shift in the pharmacological management of VTE during recent years (4). All four DOACs are non-inferior to VKA in the prevention of recurrent VTE event and superior to VKA with regard to bleeding events (5). Therefore, international guidelines recommend DOAC therapy over VKA therapy following acute VTE (6).